Cyber Marketing Model : Produk UMKM Wilayah Medan-Binjai-Deli Serdang Propinsi Sumatera Utara - Hazmanan Khair; Delyana Rahmawani Pulungan; Linzzy Pratami Putri (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
This study aims to help SMEsowner who are domiciled in Medan, Binjai, and Deli Serdang (MEBIDANG) in expanding the market for products produced by using the website as a more efficient and effective marketing tool for customers. The designing this website using the online shop principle. The problem in this research can be formulated